Influence of Exogenous Sucrose on Total Phenolic, Vitamin C and Antioxidant Enzymes of Soybean (Glycine max L.) Sprouts - Uthai, Narissara; Rojsuntornkitti, Kamonwan; Jittrepotch, Nitipong; Santakul, Ataya; Phanumong, Putkrong; Kraboun, Kitisart (Journal of Food Health and Bioenvironmental Science, 2023)
This research explained the effect of exogenous sucrose on the levels of DPPH free radical scavenging ability, total phenolics and vitamin C as well as the L-galactono-1,4-lactone dehydrogenase (GalLDH), superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) activities of soybean (Glycine max L.) sprouts. Soybean seeds were soaked in the various solutions prepared with 0, 1, 10 and 100 mM sucrose at 25°C for 12 hr and then sprayed with these solutions every 12 hr during the germination for 5 days. The higher concentration of exogenous sucrose decreased the L* value of soybean sprouts; whereas, the levels of DPPH free radical scavenging ability, total phenolic, vitamin C and GalLDH, SOD, CAT and APX activities increased. The soybean sprouts from 100 mM sucrose-treated seeds showed the maximum levels of DPPH free radical scavenging ability, total phenolics, vitamin C and GalLDH, SOD, CAT and APX activities, i.e. 85%, 164.95 mg GAE g-1 FW, 120.65 mg 100g-1 FW, 25.32 U g-1FW, 12.00 U g-1FW, 25.36 U g-1FW and 924 U g-1FW, respectively. Thus, it suggested that the sucrose treatment helped to promote the soybean sprouts in containing high-levels of antioxidant activities.